Comparative analysis of pathological and toxicological features of opiate overdose and non-overdose fatalities - Soravisut N. (2014)
Objective: To compare pathological and toxicological features between opiate overdose and non-opiate overdose fatalities examined in the Department of Forensic Medicine, Chiang Mai University, Thailand. Material and Method: A retrospective study of 142 cases, diagnosed as opiate-related deaths between 1996 and 2008 was conducted. Demographic data, pathological findings and toxicological results were retrieved from autopsy records. Results: Within these 142 opiate-related deaths, 102 cases were classified as opiate overdose fatalities by Forensic Medicine doctors. More than 95% of cases were male. About 80% were aged 20 to 39 years. Forty-eight percent were Thai, 13% were British and 11% were American. The most common places of death were residential areas and hotels. Pulmonary edema and needle marks were more common in opiate overdose cases than in non-opiate overdose cases. Toxicological findings showed that 61% of opiate overdose cases and 34% of non-opiate overdose cases were positive for blood morphine. Morphine was detected in about 95% of urine samples in both groups. About 62% of opiate overdose cases and 31% of non-opiate overdose cases had positive blood alcohol. Conclusion: The average incidence of opiate-related death was about 1% of autopsy cases. More than two thirds of the deaths were opiate overdose cases. After the year 2003, more foreigners suffered from opiate overdose fatalities than Thais. The fatalities were confined to an area frequented by tourists. Pulmonary edema and needle puncture marks were more frequently observed in opiate overdose cases. The number of cases of morphine detection in serum from the opiate overdose group was significantly higher than in the non-opiate overdose group. There was no significant difference in urine morphine detection between both groups. Other substances detected in these victims were alcohol, benzodiazepines, methamphetamine, methylenedioxymethamphetamine and methadone. Alcohol was found significantly higher in opiate overdose fatality than in non-opiate overdose deaths.